Многофункциональный сенсор с цифровой индикацией - Vikulin, I. M.; Ilyin, S. V.; Mingalev, V. A. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The paper proposes a sensor circuit containing a generator based on a unijunction transistor with a sensitive element, the current through which depends on a specific external influence — temperature, pressure, radiation, etc. The change in current through the element leads to a change in the frequency of output pulses, which are read by counters with information output to a light display. An example of a temperature sensor implementation based on this scheme is provided.